Understanding the Differences and Meeting Points between Shia and Sunni - Sabaruddin Sabaruddin; Hamzah Harun Ar Rasyid (Lembaga Sembilan Tiga Community, 2023)
The purpose of this research is to explore the differences between Shia and Sunni perspectives, including their understanding and concepts. The study uses a qualitative approach with library research and data collection through reference materials. The data is analyzed through data reduction, presentation and conclusions, while data validity is ensured through the triangulation method. The results of the research indicate that Shia refers to supporters of Ali bin Abi Talib, while Sunni adheres to al-Sunnah wa al-Jama'ah or Ahlus-Sunnah wal Jama'ah, which is commonly abbreviated as Ahlul-Sunnah. While both groups use the Qur'an and al-Sunnah as the basis of their understanding, the interpretation and understanding differ. The differences between Shia and Sunni lie only in their methods of understanding and explaining furiyah. Despite these differences, both groups adhere to the Al-Qur'an and Al-Hadith.